Combustion process and NOx emissions of a marine auxiliary diesel engine fuelled with waste cooking oil biodiesel blends. (1st February 2018) - Wei, Lijiang; Cheng, Rupeng; Mao, Hongjun; Geng, Peng; Zhang, Yanjie; You, Kun
Abstract: In order to reduce the harmful emissions from marine diesel engines, the use of alternative fuels is a promising option. In this study, the combustion process and NOx emissions and composition ratios of waste cooking oil biodiesel on a marine auxiliary diesel engine were investigated experimentally. Four different blended ratios of biodiesel and diesel were selected. The results showed that the peak of heat release rate (PHRR) decreased with the increasing biodiesel blended ratios at most of the operation conditions. The maximum reductions of PHRR were 11.04% and 19.86% at speeds of 1050 rpm and 1500 rpm. The brake specific fuel consumption (BSFC) increased but the brake thermal efficiency (BTE) changed little when the biodiesel blended ratio increased. The maximum increments of BSFC were reached at B50 and were 7.0%–8.3% and 5.1%–6.1% at 1050 rpm and 1500 rpm under different engine loads. With the increase of biodiesel blended ratios, NOx emissions decreased and NO2 /NOx increased slowly due to the decline of in-cylinder temperature. While NO2 /NOx decreased significantly with the increasing engine speed and load for the reduction of in-cylinder cooler regions. In general, the waste cooking oil biodiesel can be considered as an alternative fuel for marine auxiliary diesel engines. Highlights: The impact of waste cooking oil biodiesel on a marine auxiliary diesel is studied. Physicochemical properties and elemental composition of the biodiesel are detected. NOx emissions and composition ratios are analyzed. NO2 /NOx is mainly affected by the operation conditions.